2013
DOI: 10.1002/oby.20511
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss after bariatric surgery in morbidly obese adolescents with MC4R mutations

Abstract: Objective To determine the frequency of Melanocortin4 Receptor (MC4R) mutations in morbidly obese adolescents undergoing bariatric surgery and compare weight loss outcomes in patients with and without mutations. Design and Methods In this prospective cohort study, 135 adolescent patients evaluated for bariatric surgery were screened for MC4R mutations; 56 had 12 month postoperative data available for analysis. Results MC4R mutations were detected in five of the 135 patients (3.7%); four underwent restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Laparoscopic adjustable gastric banding did not result in a long-term weight reduction in an 18-years old patient with complete MC4R deficiency [217], and was associated with a high risk of conversion to bypass operations in individuals with partial MC4R deficiency [218]. On the other hand, three studies confirmed that Roux-en-Y gastric bypass surgery was an efficient strategy to lose weight in MC4R mutation carriers [219][220][221]. These results suggest that diversionary operations, which are more invasive but more efficiently improve the neurohormonal control of satiety than gastric banding procedures, be recommended in the context of non-syndromic monogenic forms of hyperphagic obesity.…”
Section: Obesity-predisposing Gene Variants Interact With Bariatric Smentioning
confidence: 84%
“…Laparoscopic adjustable gastric banding did not result in a long-term weight reduction in an 18-years old patient with complete MC4R deficiency [217], and was associated with a high risk of conversion to bypass operations in individuals with partial MC4R deficiency [218]. On the other hand, three studies confirmed that Roux-en-Y gastric bypass surgery was an efficient strategy to lose weight in MC4R mutation carriers [219][220][221]. These results suggest that diversionary operations, which are more invasive but more efficiently improve the neurohormonal control of satiety than gastric banding procedures, be recommended in the context of non-syndromic monogenic forms of hyperphagic obesity.…”
Section: Obesity-predisposing Gene Variants Interact With Bariatric Smentioning
confidence: 84%
“…We also reported outcomes of laparoscopic adjustable gastric banding (AGB) in 19 MC4R variant carriers, who had poorer outcomes at 3 years than noncarriers (10). This work has been followed by numerous conflicting publications regarding eating behavior and surgical outcomes in patients with rare and common genetic variants in MC4R (11)(12)(13)(14)(15)(16)(17)(18)(19). Main confounds are short follow-up, absence of stratification for sex and age, and underpowered study designs that impede analyses of mechanisms, potentially affecting outcomes (19).…”
mentioning
confidence: 99%
“…In contrast, morbidly obese adolescent patients with heterozygous MC4R mutations experienced weight loss after restrictive bariatric surgery procedures that was no less than the weight lost by controls without the MC4R mutations [14]. No weight-loss maintenance occurred other than post-operative care instructions advising patients to follow a standard restrictive dietary protocol of initially a diet that was pureed, then one that was blended followed by a soft diet, and beyond that, a well-balanced low-fat diet.…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 98%
“…Patients with the loss-of-function (LOF) MC4R mutation experience an increased appetite or hyperphagia, which may start in childhood. These mutations are considered to limit the extent to which weight loss or the maintenance of weight loss occurs with different weight reduction methods such as lifestyle intervention in children [11] and bariatric surgery for adolescent and adult patients [12][13][14].…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 99%